Monitoring Medication Adherence by Unannounced Pill Counts Conducted by Telephone: Reliability and Criterion-Related Validity - Kalichman, Seth C. (2008)
BACKGROUND: Although demonstrated valid for monitoring medication adherence, unannounced pill counts conducted in patients’ homes are costly and logistically challenging. Telephone-based unannounced pill counts offer a promising adaptation that resolves most of the limitations of home-based pill counting. PURPOSE: We tested the reliability and validity of a telephone-based unannounced pill count assessment of antiretroviral adherence. METHODS: HIV positive men and women (N = 89) in Atlanta GA completed a telephone-based unannounced pill count and provided contemporaneous blood specimens to obtain viral loads; 68 participants also received an immediate second pill count conducted during an unannounced home visit. RESULTS: A high degree of concordance was observed between the number of pills counted on the telephone and in the home (Intraclass Correlation, ICC, = .981, p < .001) and percent of pills taken (ICC = .987, p < .001). Adherence obtained by the telephone count and home count reached 92% agreement, Kappa coefficient = .94. Adherence determined by telephone-based pill counts also corresponded with patient viral load, providing evidence for criterion-related validity. CONCLUSIONS: Unannounced telephone-based pill counts offer a feasible objective method for monitoring medication adherence.